Meta-Analysis of Parent Training Programs Utilizing Behavior Intervention Technologies - Kimberly B. Bausback; Eduardo L. Bunge (Social Sciences, 2021)
Behavioral Parent Training (BPT) traditionally occurs in face-to-face (FTF BPT). Recently, Behavioral Intervention Technology (BIT) has been developed to deliver BPT in lieu of or as an adjunct to FTF BPT using websites, computer software, smartphone applications, podcasts, pre-recorded sessions, and teletherapy. The present meta-analysis reviews BIT BPT randomized control and comparison studies to determine the overall efficacy of BITs, if the level of human support significantly effects BIT BPT treatment outcomes, and which populations BIT BPT are effective for, by analyzing the following study variables: socioeconomic status, race, and clinical population. The analyses indicated that, overall, BIT BPT is an effective treatment (g = 0.62), and did not indicate a significant difference between levels of human support (χ2 (3) = 4.94, p = 0.18). Analysis did indicate a significant difference between studies that used waitlist or education control groups, compared to studies that used active treatment controls (χ2 (1) = 12.90, p = 0.00). The analyses did not indicate a significant difference between clinical population, low socioeconomic status, and racial minority studies. These findings provide preliminary evidence that BIT BPT is effective for treating child and adolescent externalizing behavior in a variety of populations.